2012
DOI: 10.1371/journal.pone.0029845
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Genetic Diversity of Cherimoya (Annona cherimola Mill.): Application of Spatial Analysis for Conservation and Use of Plant Genetic Resources

Abstract: There is a growing call for inventories that evaluate geographic patterns in diversity of plant genetic resources maintained on farm and in species' natural populations in order to enhance their use and conservation. Such evaluations are relevant for useful tropical and subtropical tree species, as many of these species are still undomesticated, or in incipient stages of domestication and local populations can offer yet-unknown traits of high value to further domestication. For many outcrossing species, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 59 publications
1
77
0
10
Order By: Relevance
“…Bootstrap analysis with 1000 replicates (Felsenstein, 1985) was performed to get the confidence level of the tree. Additionally, all alleles per locus were georeferenced for spatial distribution following van Zonneveld et al (2012). A grid for allelic richness parameter was generated using the DIVA-GIS 7.5 software with a cell size grid of 0.05 minutes (which corresponds to approximately 0.1 km in the study area) and applying a circular neighborhood with a 0.5 degrees diameter (corresponding to approximately 55.5 km).…”
Section: Statistical and Genetic Analysesmentioning
confidence: 99%
“…Bootstrap analysis with 1000 replicates (Felsenstein, 1985) was performed to get the confidence level of the tree. Additionally, all alleles per locus were georeferenced for spatial distribution following van Zonneveld et al (2012). A grid for allelic richness parameter was generated using the DIVA-GIS 7.5 software with a cell size grid of 0.05 minutes (which corresponds to approximately 0.1 km in the study area) and applying a circular neighborhood with a 0.5 degrees diameter (corresponding to approximately 55.5 km).…”
Section: Statistical and Genetic Analysesmentioning
confidence: 99%
“…An important step towards improving the on-farm conservation of any species is having data about its current (and potential) distribution and cultivation. In addition to individuals' knowledge on these aspects, publicly available georeferenced data is a powerful starting point for studies on a crop's agroecological potential and adaptive capacity which in turn are useful for planning in situ conservation initiatives [33][34][35]. Searches performed in the data portal of the GBIF resulted in retrieval of georeferenced data for almost all the species.…”
Section: Limited Knowledge On the Species' Distribution And Productionmentioning
confidence: 99%
“…Based on a subset of 9 simple sequence repeats (SSRs), selected from 52 polymorphic SSR markers from cherimoya [9], in combination with Geographic Information Systems (GIS) techniques, van Zonneveld et al [19] studied spatial patterns of genetic diversity of semi-cultivated and wild cherimoya trees in the Ecuadorian, Peruvian and Bolivian Andes. The latter authors found that allelic richness, locally common alleles and expected heterozygosity are high in the putative centre of origin (southern Ecuador and northern Peru).…”
Section: Introductionmentioning
confidence: 99%